2020
DOI: 10.1186/s12887-020-02342-z
|View full text |Cite
|
Sign up to set email alerts
|

Extended spectrum beta-lactamase and fluoroquinolone resistance genes among Escherichia coli and Salmonella isolates from children with diarrhea, Burkina Faso

Abstract: Background The emergence and spread of multidrug-resistant gram-negative bacteria (MDR) has become a major public health concern worldwide. This resistance is caused by enzymes-mediated genes (i.e., extended spectrum beta-lactamases) that are common in certain Enterobacterioceae species. However, the distribution of these genes is poorly documented in Burkina Faso. This study aims to determine the prevalence and distribution of the resistant genes coding for broad spectrum beta-lactamases and q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 46 publications
3
25
5
Order By: Relevance
“…Our results showed 19.4% of SHV-type ESBL producing E. coli which is a little similar to 21% detected in Pakistan [42]. By cons, this prevalence is higher than 0% [9] and 5.9% [17], previously reported in Burkina Faso but lower than 45% reported in Iran [27]. The bla CTX−M gene (Fig.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Our results showed 19.4% of SHV-type ESBL producing E. coli which is a little similar to 21% detected in Pakistan [42]. By cons, this prevalence is higher than 0% [9] and 5.9% [17], previously reported in Burkina Faso but lower than 45% reported in Iran [27]. The bla CTX−M gene (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, OXA-type ESBL producing DEC strains (38.7%) was the most frequently detected ESBL gene. This prevalence is lower than that reported in our previous study in rural area of Burkina Faso: 100% [9], also lower comparatively to 52% reported in Pakistan [42]. However, a recent study in young children reported 3% of commensal E. coli bearing the bla OXA gene in Bangladesh [41].…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…In addition, the E. coli O157:H7 also produce extendedspectrum beta-lactamases (ESBLs), which render them resistant to many antibiotics and these strains have been widely reported in recent years on a global scale [9]. Indeed, Enterobacteriaceae that produce ESBLs are linked to higher rates of morbidity and mortality, longer hospital stays, and higher healthcare costs [10]. According to previous reports ESBL have been related to the development of antibiotic-resistant bacterial strains and due to the spread of these strains, antimicrobials used to treat patients with pathogen bacteria such as E. coli are likely to become less successful [11].…”
Section: Introductionmentioning
confidence: 99%